2017
DOI: 10.1186/s40807-017-0041-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of global solar radiation from meteorological data in the Sahelian zone of Chad

Abstract: The study focuses on the evaluation of global solar radiation on a horizontal level. The estimate of the solar layer was made on the basis of mathematical model obtained from the relations of Angstrom-Prescott, Allen and Sabbagh. The different proposed models have been implemented by using MATLAB and Excel. The models were evaluated using MPE, NSE, RMSE and MBE. The outcome of this shows that the Angstrom-Prescott model is the most suitable for the calculation of global solar radiation in the sites of Mongo wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In general, the value of the global solar radiation of the Sahelian zone is of the order of 6 kWh/m 2 /day. These results are similar to those obtained in the evaluation of global solar radiation made by Soulouknga et al [9] and those of the NASA database as shown in Figs. 16, 17, 18 and 19.…”
Section: Analysis Of Solar Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…In general, the value of the global solar radiation of the Sahelian zone is of the order of 6 kWh/m 2 /day. These results are similar to those obtained in the evaluation of global solar radiation made by Soulouknga et al [9] and those of the NASA database as shown in Figs. 16, 17, 18 and 19.…”
Section: Analysis Of Solar Parameterssupporting
confidence: 92%
“…In general, on a horizontal plan, the relation of Klein [24] defines the solar radiation (H0) outside the atmosphere as: (9) where:…”
Section: Global Solar Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum average solar radiation for the most part of the country is said to be about 5.3 KWh/m 2 /day [6]. In the past, a large number of researchers have used Sun shine based empirical equation and Angstrom-type correlation model to estimate the global solar radiation on a horizontal surface [7][8][9][10][11][12][13]. There is no finding that have been done before at a kombolcha sites to estimate the global solar radiation using the sun-shine and temperature based empirical equations.…”
Section: Introductionmentioning
confidence: 99%
“…The weather parameters are the ambient temperature, the relative humidity, the sunshine duration. Amongst the astronomical parameters one has the maximum duration of the day, the variation of the sun, the variation of the ground-sun distance and the solar radiation in the extraterrestrial radiation [20]. As part of this work, these include the Angstrom-Prescott model, the Allen model and the Sabbagh model.…”
Section: Used Modelsmentioning
confidence: 99%